Seorang Penderita Sistemik Lupus Eritematosus Dengan Miokarditis Akut - I Gede Yudha Kartika I Gede Yudha Kartika (Yayasan Pendidikan Medika Indonesia, 2022)
Systemic lupus erythematosus (SLE) is a classic autoimmune disease in which the complex interactions of apoptotic disorders, upregulation of the innate and adaptive immune systems, activation of complement, immune complexes and inflammation of the tissues lead to autoimmune processes. Cardiovascular disease (CVD) risk factors and markers appear to provide a statistical explanation for the high risk of CVD in SLE. Markers of inflammation such as acute-phase reactants include CRP and PAF-acetylhydrolase, dyslipidemia, Triglycerides (TG) and High Density Lipoprotein (HDL)), elevated LDL, antiphospholipid antibodies (aPL; lupus anticoagulant), kidney disease and hypertension. Overall, a combination of traditional and non-traditional risk factors might explain the increased risk of CVD in people with SLE. Given the high risk of cardiovascular disease in patients with SLE, a proactive approach should be taken in the management of risk factors. A holistic approach for patients with SLE should include an assessment of risk factors so that lifestyle, weight, smoking and exercise are taken into account and dietary controls can help improve dyslipidemia.